PERILAKU APARATUR SIPIL NEGARA DALAM MEMBERIKAN PELAYANAN PRIMA (EXCELLENT SERVICE) PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KOTA KENDARI - Muhammad Amir; Sitti Hairani Idrus; Ardot Ardot (Journal Publicuho, 2019)
This study aims to determine and describe the behaviour of the State Civil Apparatus in providing services and describing the Implementation of Excellent Services at the One-stop Investment and Integrated Services Office of Kendari City. The research method used is descriptive qualitative research, a description of the results of interview observations and documentation studies, so as to be able to describe various matters relating to the Behavior of State Civil Apparatuses in Providing Excellent Service. The results showed that the behaviour of the State Civil Apparatus in providing Prime services in terms of the dimensions of receiving, responding, respecting and being responsible for providing services to service users had gone quite well, but the implementation was not optimal because there were still found several employees who had not shown behaviour and good treatment to the community. Implementation of excellent service in terms of dimensions of service procedures, service costs, completion time, service products, facilities, infrastructure, competency of service providers as a whole is good